THE FUNCTIONS OF THE PERIPHRASES AND ITS TYPES IN THE ENGLISH AND UZBEK LANGUAGE TEXTS - Seilxanova Rita Nurniyazovna (Journals Park Publishing, 2022)
In this article is devoted to the types of the periphrases and their functions in the English and Uzbek languages in the various texts.
Keywords: genuine; periphrases; circumlocution